2018
DOI: 10.1002/cpe.5105
|View full text |Cite
|
Sign up to set email alerts
|

The new Multicast Repair (M‐REP) IP fast reroute mechanism

Abstract: Summary The network convergence time may take hundreds of milliseconds or more. Since this repair performance may be unsatisfactory, IP fast reroute (IPFRR) approaches have been developed to decrease the network convergence time and minimize traffic loss. These IPFRR mechanisms are usually based on the proactive precomputation of a backup path before a failure occurs. Once a failure is detected, the router running IPFRR will immediately use this backup path in response to the failure, rather than computing a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The reactive IP Fast Reroute mechanisms include only Multicast Repair (M-REP) [57] and Enhanced M-REP [58].…”
Section: Related Workmentioning
confidence: 99%
“…The reactive IP Fast Reroute mechanisms include only Multicast Repair (M-REP) [57] and Enhanced M-REP [58].…”
Section: Related Workmentioning
confidence: 99%
“…We have been analyzing and researching FRR mechanisms for several years [ 21 , 56 , 57 , 58 , 59 , 60 , 61 ]. Based on the obtained results, we can summarize the most significant properties of the existing FRR mechanisms in Table 1 .…”
Section: Related Workmentioning
confidence: 99%
“…The research question we faced was whether this modification could cause micro-loops. The verification was performed using the mathematical proof by a contradiction [ 56 ], which confirmed that the modification does not cause routing loops. However, the M-REP mechanism operates in topologies which must meet two conditions, the network topology must use point-to-point links only and the target of original protected flow must be directly connected to router D.…”
Section: M-rep Frr Mechanismmentioning
confidence: 99%
“…An overview of the basic parameters of existing FRR solutions as the output of our research in this area [ 18 , 38 , 45 , 46 , 47 ] is summarized in Table 1 . In this table, we compared the most important properties of existing FRR mechanisms such as repair coverage, proactive behavior, dependency on link-state routing protocols, and prediction.…”
Section: Related Workmentioning
confidence: 99%